(-2x^2 +3x -7) y= -2x^2 +3x +17
(-4x+3)y + (-2x^2+3x-7)y' = -4x+3
y' = (4x-3)(y-1)/(2x^2-3x+7)
y'(-1,-1) = (-7)(-2)/(2+3+7) = 7/6
---------------------------------
doing the long division,
y = (2x^2-3x-17)/(2x^2-3x+7)
= 1 - 24/(2x^2-3x+7)
y' = 24(4x-3)/(2x^2-3x-7)^2
y'(-1) = 24(-7)/12^2 = -7/6
--------------------------------
using the quotient rule,
y = (2x^2-3x-17)/(2x^2-3x+7)
y' = [(4x-3)(2x^2-3x+7)-(2x^2-3x-17)(4x-3)]/(2x^2-3x+7)^2
= 24(4x-3)/(2x^2-3x+7)^2
---------------------------------
The tangent line is thus y+1 = -7/6 (x+1)
Check the graphs at
http://www.wolframalpha.com/input/?i=plot+(2x%5E2-3x-17)%2F(2x%5E2-3x%2B7),+y%3D(-7%2F6)(x%2B1)-1
Consider the function:(-2x^2 +3x -7) y= -2x^2x +3x +17
Find y ′ using implicit differentiation. Do not solve for y.
What is the slope of the tangent at (x,y) = (−1,−1)?
Find y ′ by solving for y and using the quotient rule.
What is the slope of the tangent when x = -1 ?
Thanks for your help.
1 answer